2016
DOI: 10.1051/0004-6361/201629590
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA detection of CO rotational line emission in AGB stars in the Large Magellanic Cloud

Abstract: Context. Low-and intermediate-mass stars lose most of their stellar mass at the end of their lives on the asymptotic giant branch (AGB). Determining gas and dust mass-loss rates (MLRs) is important in quantifying the contribution of evolved stars to the enrichment of the interstellar medium. Aims. Attempt to, for the first time, spectrally resolve CO thermal line emission in a small sample of AGB stars in the Large Magellanic Cloud. Methods. The Atacama Large Millimeter Array was used to observe 2 OH/IR stars … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 65 publications
5
43
1
Order By: Relevance
“…For their LMC sample with OH 1612 MHz line emission, Goldman et al (2017) concluded that at similar luminosity the LMC sources have lower υ ∞ (they center around 10 km s −1 ) than those of their Galactic comparison samples. The CO line detections of four carbon stars in the LMC by Groenewegen et al (2016) are consistent with this conclusion.…”
Section: The Magellanic Cloudssupporting
confidence: 81%
“…For their LMC sample with OH 1612 MHz line emission, Goldman et al (2017) concluded that at similar luminosity the LMC sources have lower υ ∞ (they center around 10 km s −1 ) than those of their Galactic comparison samples. The CO line detections of four carbon stars in the LMC by Groenewegen et al (2016) are consistent with this conclusion.…”
Section: The Magellanic Cloudssupporting
confidence: 81%
“…In (metal-poor) globular clusters and the Magellanic Clouds, the onset appears between 700 and 1500 L⊙ McDonald et al 2011a,c;Boyer et al 2015). While the total mass-loss rate (at least in older stars) does not appear to be strongly linked to metallicity (van Loon et al 2008;, the onset luminosity is likely to have some metallicity dependence (e.g McDonald et al 2010b), as the dust column density should scale approximately with metallicity (van Loon 2006; Groenewegen et al 2016). However, the onset is hard to trace in solar metallicity populations due to distance or contamination.…”
Section: Application To Mass-losing Stars On the Giant Branchmentioning
confidence: 99%
“…For the SMC the metallicity value is taken from Rubele et al (2018), while for the LMC carbon stars we select the typical value derived from trilegal simulations (Girardi et al 2005) based on the star formation history derived by Harris & Zaritsky (2009) (Marigo, private communication). The same reference value for the LMC has been assumed in other works (Groenewegen et al 2016a;Lebzelter et al 2018). For the Z = 0.004 the spectra have been calculated by employing a denser sampling of dust density profile employed in the radiative transfer calculations with respect to Nanni et al (2018).…”
Section: Model and Grid Parametersmentioning
confidence: 99%
“…For each of the sources the initial and current stellar masses are constrained by employing the TP-AGB tracks from Marigo et al (2013) with initial masses of 1.8 and 3.0 M ⊙ , and metallicity Z = 0.006. The same procedure as in Groenewegen et al (2016b) is adopted: the current mass of the star is the one of the model in the track with the period and luminosity closer to the observed ones. The luminosity value adopted is the one derived from this work.…”
Section: Carbon Stars In the Lmc Observed With Almamentioning
confidence: 99%
See 1 more Smart Citation